2021
DOI: 10.1002/cnr2.1398
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety profile of pembrolizumab for metastatic urothelial cancer: A retrospective single‐center analysis in Japan

Abstract: Background: The paradigm of medical treatment for metastatic urothelial carcinoma is dramatically changing through the introduction of pembrolizumab. Aim:We investigated the treatment effectiveness, the safety profile, and the prognostic factors of pembrolizumab in Japanese real-world clinical practice. Methods and results:The medical records of 74 consecutive Japanese patients with metastatic urothelial cancer (UC), who started pembrolizumab as a secondor later-line treatment at our institution between Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The survival benefit of immunotherapy in both untreated and pretreated patients with mUC has been observed regardless of all of those clinical factors, confirming their prognostic but not predictive value, in many retrospective analyses [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ] and subgroup and post-hoc analyses of prospective randomised trials [ 71 , 72 ].…”
Section: Clinical Factorsmentioning
confidence: 80%
“…The survival benefit of immunotherapy in both untreated and pretreated patients with mUC has been observed regardless of all of those clinical factors, confirming their prognostic but not predictive value, in many retrospective analyses [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ] and subgroup and post-hoc analyses of prospective randomised trials [ 71 , 72 ].…”
Section: Clinical Factorsmentioning
confidence: 80%
“…In this study, though favorable ORR, OS, and PFS were observed in patients with a CRP flare response, it was not possible to reveal the differences in oncological outcomes between flare-responder and responder groups using multivariable analysis because of the small number of patients and absence of progression or death in patients with a CRP flare response during the study period. However, patient backgrounds including the factors associated with treatment efficacy (3)(4)(5)(6)(7)(8)17) among each group were not significantly different, and the CRP flare response might be an important factor to predict favorable oncological outcomes. In clinical practice, therefore, pembrolizumab should be continued in patients with a CRP flare response, when irAEs are manageable.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, various biomarkers including blood cell count markers (11) or nutritional status-based markers such as prognostic nutritional index (12) were reported in pembrolizumab therapy for patients with advanced UC. Several studies on UC have reported that elevated CRP levels before surgery (13), chemotherapy (14,15), or ICIs treatment (3,7,8) were associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations